Myofibroblasts emerge during alveolar regeneration following influenza-virus-induced lung injury - Khadim, Ali; Kiliaris, Georgios; Vazquez-Armendariz, Ana Ivonne; Procida-Kowalski, Tara; Glaser, David; Bartkuhn, Marek; Malik, Tanya; Chu, Xuran; Moiseenko, Alena; Kuznetsova, Irina; Ahmadvand, Negah; Lingampally, Arun; et al. (My University, 2025)
Alveolar regeneration requires the coordinated engagement of epithelial stem cells and mesenchymal niche cells to restore the intricate alveolar architecture of the lung. The current paradigm is that certain aspects of lung organogenesis are mimicked during injury repair in the adult stage. Here, we employ a longitudinal single-cell transcriptomic survey to fate map lung mesenchymal cells throughout development and adulthood. We show that myofibroblasts that are reminiscent of developmental alveolar myofibroblasts (AMFs), termed AMF-like cells, are activated during alveolar regeneration following influenza-virus-induced lung injury. Although AMF-like cells share a similar transcriptomic signature with myofibroblasts that are associated with aberrant repair and fibrosis, these cells do not derive from fibroblast growth factor 10-positive alveolar fibroblasts, and their dysregulation is associated with failed alveolar regeneration in humans. Our data emphasize the role played by developmental mechanisms in alveolar regeneration and highlight the context-dependent nature of myofibroblast biology and function during injury repair.
Keywords: ddc:610